AN ANALYSIS OF CODE-SWITCHING IN THE MOVIE “LUCA” - Kezia Anindita (ELTR Journal, 2023)
Code-switching is a socio-linguistic phenomenon that often happens in our daily life. This study is conducted to analyse code-switching that happen in the movie “Luca”, which is the most streamed movie in 2021. There are two research questions of this study, which are what are the types of code-switching used in the movie? And what are the functions of the code-switching used in the movie? The qualitative method is used in this study. To collect the data, the researcher will search for the movie and the movie’s script on the internet. After collecting the data, the researcher will watch the movie while reading the script. Then, search the meaning of each code-switching, and group the types and functions. The study found that there are three types of code-switching used in the movie which are inter-sentential, intra-sentential, and tag-switching. The most frequent code-switching types used are inter-sentential and tag-switching, which are 39,72% and 20,56%. There are 4 types of code-switching used in the movie, which are referential, directive, expressive, and phatic functions. The most frequent code-switching function used is directive, which is 38,35%.